Constructing balleans - Banakh, T.; Protasov, I. (Український математичний вісник, 2018)
A ballean is a set endowed with a coarse structure.We introduce and explore three constructions of balleans from a pregiven family of balleans: bornological products, bouquets, and combs. We analyze also the smallest and largest coarse structures on a set X compatible with a given bornology on X.